Pharmacophore-based virtual screening for identification of marine sponge bioactive compound inhibitors against Alzheimer's disease - Suruthi SS; Prashanth KK; Baskaran A (Chemical Physics Impact)
Alzheimer's disease is a hereditary neurodegenerative disease that occurs sporadically and causes amnestic cognitive impairment. Traditional drug discovery methods have faced challenges in this regard, leading researchers to explore natural products as potential therapeutics. Marine sponges are rich in diverse range of bioactive compounds with promising biological activities. In this study, AChE, SLC6A4, 5-HT1A, TrkB, and GABA are chosen as the target proteins, which focuses on ache, serotonin, GABA, and neurotropic pathways. A bioactive compound library from marine sponges was prepared by retrieving a list from the CMNP database. The compounds were screened using a chronological index and Drug likeness rules where 2,504 compounds were filtered out based on their molecular weight and the selected compounds undergone secondary screening using pharmacology filters to assess their absorption, distribution, metabolism, and excretion (ADME) properties. Virtual screening was performed using PyRx with selected target proteins. Four compounds namely Xestosaprol D, Xestosaprol E, Xestosaprol J, and 14, 15-dihydroxymethyl Xestoquinone were found to interact with all the chosen protein. Among 4 compounds, Xestosaprol J showed better binding energy of -7.7, -9.9, -8.4, -9.2, and -8.1 kcal/mol. Further, the best interacting AchE-Xestosaprol J complex along with standard AchE Agonist Donepezil was subjected to Molecular dynamics simulation and analysis, which maintained its stability between 65 and 85 ns with RMSD value ranging between 0- 3.5 Å in the virtual biological environment. Overall, Xestosaprol J showed better physicochemical and ADME properties, suggesting their potential as drug candidates, but further investigations are needed to determine their specific biological activities in-vitro.